A Review on Social Entrepreneurship - Puspita, Amelia Tri (SMART Insight, 2022)
The problem of unemployment is a problem faced by every country, as is the case in Indonesia, the problem of unemployment and labor in Indonesia is still a problem that needs to be addressed seriously. The large unemployment rate can certainly cause social problems, namely poverty. One way to overcome the social problems that are currently of great concern to developing countries including Indonesia is to develop social entrepreneurship or popularly known as social entrepreneurship. This study aims to determine the development map and trend of Social Entrepreneurship published by reputable journals in the field of Economics and Finance. The data analyzed are more than 1594 Dimensions indexed research publications. The export data was then processed and analyzed using the R Biblioshiny application program to determine the bibliometric map of Social Entrepreneurship development. The results showed that the number of publications on this topic continues to increase.